External pressure induced buckling collapse of high density polyethylene (HDPE) liners: FEM modeling and predictions - Rueda, Federico (2015)
Abstract Thermoplastic polymers such as HDPE are nowadays widely used as lining materials for oil and gas pipelines. However, during maintenance or unexpected service stoppages, these liners can undergo external pressure induced bucking collapse. The objective of this work is to assess the mechanical response of HDPE liners undergoing buckling collapse by means of Finite element modeling (FEM) simulations on Abaqus 6.10. To accomplish this, an advanced constitutive model, namely the Three Network Model (TNM) was employed. In order to determine the input parameters for the model, a series of tensile and compressive uniaxial tests were conducted. The suitability of the model for this particular application was assessed by contrasting the simulation and the experimental results of a diametral compression test. The complex strain rate and pressure dependent mechanical response of HDPE liners was analyzed by modeling the buckling collapse dynamic event as an increasing volume of fluid entering the gap cavity between liner and host pipe. The model predictions allowed establishing a mathematical relationship between the depressurization velocity of the tubes and the resulting collapse pressure. These relations can be used to improve the current design guidelines for plastic liners.